2001
DOI: 10.1007/bf02900596
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of “all-fish” growth hormone gene trans ferred carp (Cyprinus carpio L.) and its F1 generation

Abstract: Recombinant "all-fish" growth hormone gene (GH) was microinjected into the fertilized eggs of carp. A comparison between the growth traits of transgenics and non-transgenics was carried out, and the transgenic individuals with significant "fast-growing" effect were successfully gained. A comparison on the reproductivities was also given out between the transgenics and their non-transgenic siblings, and showed that the reproductive capacity of transgenics was substantially equivalent to those of the non-transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(105 citation statements)
references
References 8 publications
2
99
0
4
Order By: Relevance
“…This construct contains the recombinant sequence of the grass carp Ctenopharyngodon idellus (Cuvier & Valenciennes) growth hormone gene driven by a common carp β-actin gene promoter (Wang et al, 2001). F 5 'all-fish' GH transgenic carp used in the present study were produced on April 25, 2007, from crosses between a wild-type female and a F 4 'all-fish' GH transgenic male of a fast-growing transgenic strain as reported in previous studies (Fu et al, 2007a;Li et al, 2007).…”
Section: Experimental Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…This construct contains the recombinant sequence of the grass carp Ctenopharyngodon idellus (Cuvier & Valenciennes) growth hormone gene driven by a common carp β-actin gene promoter (Wang et al, 2001). F 5 'all-fish' GH transgenic carp used in the present study were produced on April 25, 2007, from crosses between a wild-type female and a F 4 'all-fish' GH transgenic male of a fast-growing transgenic strain as reported in previous studies (Fu et al, 2007a;Li et al, 2007).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…At the age of 16 weeks, the transgenic fish were transferred to our lab and held under flow through conditions in 1000 l tanks. Transgene positive individuals were identified by the PCR procedure of Wang et al (2001), using DNA extracted from tail fins. Non-transgenic controls were size-matched fish transported to the laboratory at approximate 20 weeks of age.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…The "all-fish" gene construct pCAgcGHc included the grass carp (Ctenopharyngodon idellus) GH cDNA (gcGHc) driven by the β-actin gene promoter of common carp (Cyprinus carpio L.), which was modified from the construct pCAgcGH (Zhu, 1992;Wang et al, 2001). The production of P 0 and F 1 "all-fish" GH transgenics was described in detail by Wang et al (2001).…”
Section: Production Of Transgenic Fishmentioning
confidence: 99%
“…The production of P 0 and F 1 "all-fish" GH transgenics was described in detail by Wang et al (2001). In brief, P 0 transgenics were produced by microinjection of pCAgcGHc into the fertilized eggs of Yellow River carp (C. carpio L.) (for details of gene transfer, see Zhu et al, 1989).…”
Section: Production Of Transgenic Fishmentioning
confidence: 99%
“…Since the transgenic founders received randomly and mosaically integrated transgenes as described by our previous studies [4], the transgenic offspring derived from hybridization between transgenic individuals will contain various integration patterns. In previous studies, e.g., it was found that two or three integration sites existed in the genome of P0 transgenic common carp [23] and widespread mosaicism existed in transgenic founders of rainbow trout (Oncorhynchus mykiss) [24]. (2) Recombination during the course of integration and germline transmission.…”
Section: Germline Transmission Of Transgene To F4 Offspringmentioning
confidence: 99%